2014
DOI: 10.1007/s00280-014-2492-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of metronomic paclitaxel/cyclophosphamide/capecitabine followed by 5-fluorouracil/epirubicin/cyclophosphamide as preoperative chemotherapy for triple-negative or low hormone receptor expressing/HER2-negative primary breast cancer

Abstract: Metronomic PCX followed by FEC chemotherapy was associated with a high pCR rate and low toxicity in TNBC patients. Further studies of this regimen in larger numbers of patients are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The clinical response rates were 90.0% and 93.9% in the intent-to-treat and per-protocol population, respectively, with a breast conservation rate of 72.7%. 60 These pCR rates were similar to response rates reported with conventional dose chemotherapy. Grade 3-4 adverse events included neutropenia (35%), leukopenia (25%), and hand-foot syndrome (8%).…”
Section: Ideal Agents and Drug Repositioningsupporting
confidence: 81%
See 1 more Smart Citation
“…The clinical response rates were 90.0% and 93.9% in the intent-to-treat and per-protocol population, respectively, with a breast conservation rate of 72.7%. 60 These pCR rates were similar to response rates reported with conventional dose chemotherapy. Grade 3-4 adverse events included neutropenia (35%), leukopenia (25%), and hand-foot syndrome (8%).…”
Section: Ideal Agents and Drug Repositioningsupporting
confidence: 81%
“…Masuda and co-authors published a phase II study of metronomic-based preoperative chemotherapy for patients with triple-negative breast cancer (TNBC) or low hormone receptor expressing/HER2-negative primary breast cancer 60 (Table 1). In total, 40 patients with primary TNBC received four cycles of paclitaxel given as a weekly metronomic schedule (80 mg/m 2 on days 1, 8, and 15) plus metronomic cyclophosphamide (50 mg/day), and capecitabine (1,200 mg/m 2 daily), followed by four cycles of conventionally dosed chemotherapy with 5-FU (500 mg/m 2 ), epirubicin (100 mg/m 2 ), and cyclophosphamide (500 mg/m 2 ) every 3 weeks.…”
Section: Ideal Agents and Drug Repositioningmentioning
confidence: 99%
“…The reason behind this is that prominent adverse effects and absence of obvious benefits in the overall survival were found in clinical trials for simultaneously administered combination chemotherapy, despite a higher tumor response rate [41-43]. However, positive tumor response and low toxicity profiles were reported in recent Phase II clinical trials on low dose metronomic drug combinations [44, 45]. These mixed clinical results of drug combination therapy present an opportunity to nanocarrier-based approaches, which are able to mitigate the problems encountered by free drug combination therapies.…”
Section: Rationales and Strategies Of Nanocarrier-based Combinatiomentioning
confidence: 99%
“…Our group previously found that the Fu-Zheng-Xiao-Liu granules could inhibit the proliferation of drug-resistant MCF-7 cells and enhance the sensitivity of drug-resistant MCF-7 cells to a combination of chemotherapy drugs. The inhibitory effect of Fu-Zheng-Xiao-Liu granules on cancer cell proliferation was dependent on the down-regulation of multidrug resistance 1 (MDR1) and P-gp expression [17–20]. …”
Section: Discussionmentioning
confidence: 99%